The Risk Management of the Bogor-Sukabumi Cross-Rail Dual-Track Construction Project on Time Control - Moerdianto, Edwin; Suryani, Fitri; Dinariana, Dwi (Interdisciplinary Social Studies, 2022)
The implementation of risk management is very important to do to reduce the occurrence of risks in the implementation. In the implementation of work, unmanaged risks can have an impact on not achieving the targets of the completion plan according to the planned time. This study aims to find out how to identify the dominant risk of time delays in the implementation of the Bogor-Sukabumi Cross Railway Double Track Construction and its handling strategies. The research conducted is descriptive research.  Primary data were collected by the method of checklist analysis from the literature, risk management of similar activity  projects or previous studies, then identified the risks. Meanwhile, the secondary data in the form of a plan map for the Bogor-Sukabumi Railway double-track route is needed as secondary data  to obtain information, project descriptions, implementation methods and the time needed to complete the construction obtained from the West Java Railway Engineering Center. The dominant risk factors that can affect performance, there are 5 risk factors, namely avalanches in the implementation of work, cost overruns related to changes and additions to work, design not in accordance with field conditions (Planning constraints), constraints related to working hours with residents around the site, and delays in obtaining planning approval.